Associations between Serum Folate Concentrations and Functional Disability in Older Adults - Lujun Ji; Tianhao Zhang; Liming Zhang; Dongfeng Zhang (MDPI AG, 2023)
Folate may have beneficial effects on physical function through its antioxidant effect. Thus, we investigated the associations between serum folate and functional disability in older adults. Data from the National Health and Nutrition Examination Survey 2011-2018 were used. Serum folate included 5-methyltetrahydrofolate and total folate. Five domains of functional disability, including lower extremity mobility (LEM), instrumental activities of daily living (IADL), activities of daily living (ADL), leisure and social activities (LSA), and general physical activities (GPA), were self-reported. Multivariable-adjusted logistic regression models and restricted cubic splines were employed. 5-Methyltetrahydrofolate was inversely associated with IADL and GPA disability, and the multivariate-adjusted ORs (95% CIs) in the highest versus lowest quartiles were 0.65 (0.46-0.91) and 0.70 (0.50-0.96), respectively. The total folate was also inversely associated with IADL (OR quartile 4vs1 = 0.65, 95% CI: 0.46-0.90) and GPA (OR quartile 3vs1 = 0.66, 95% CI: 0.44-0.99) disability. The dose-response relationships showed a gradual decrease in the risk of IADL and GPA disability as serum folate increased. In the sex, age, BMI, and alcohol consumption subgroup analyses, we saw that the associations were primarily found in females, under 80 years old, normal weight, and non-drinkers. Sensitivity analyses further confirmed the robustness of our results. Our results indicated that serum folate concentrations were negatively associated with IADL and GPA disability, especially in females. In other subgroup analyses, we discovered that these negative associations were primarily prevalent in participants under 80 years old, normal weight, and non-drinkers.